Low-Level Fluoride Exposure Increases Insulin Sensitivity in Experimental Diabetes. (July 2015) - Lobo, J.G.V.M.; Leite, A.L.; Pereira, H.A.B.S.; Fernandes, M.S.; Peres-Buzalaf, C.; Sumida, D.H.; Rigalli, A.; Buzalaf, M.A.R.
The effect of chronic fluoride (F) exposure from the drinking water on parameters related to glucose homeostasis was investigated. Wistar rats were randomly distributed into 2 groups (diabetic [D] and nondiabetic [ND]; n = 54 each). In D, diabetes was induced with streptozotocin. Each group was further divided into 3 subgroups (0, 10, or 50 mgF/L in drinking water). After 22 days of treatment, plasma and liver samples were collected. No alterations in glycemia, insulinemia, KITT, and HOMA2-IR (homeostasis model assessment 2 of insulin resistance) were seen for ND. F-exposure of D rats led to significantly lower insulinemia, without alterations in glycemia (increased %S). Proteomic analysis detected 19, 39, and 16 proteins differentially expressed for the comparisons D0 vs. D10, D0 vs. D50, and D10 vs. D50, respectively. Gene Ontology with the most significant terms in the comparisons D0 vs. D10, D0 vs. D50, and D50 vs. D10 were organic acid metabolic process and carboxylic acid metabolic process, organic acid metabolic process, and cellular ketone metabolic process. Analysis of subnetworks revealed that proteins with fold changes interacted with GLUT4 in comparison D0 vs. D10. Among these proteins, ERj3p was present in D10. Upregulation of this protein in the presence of F might help to explain the higher %S found in these animals. These data suggest that fluoride might enhance glucose homeostasis in diabetes and identify specific biological mechanisms that merit future studies.